2005
DOI: 10.1186/1477-044x-3-1
|View full text |Cite
|
Sign up to set email alerts
|

Activity of glucose oxidase functionalized onto magnetic nanoparticles

Abstract: BackgroundMagnetic nanoparticles have been significantly used for coupling with biomolecules, due to their unique properties.MethodsMagnetic nanoparticles were synthesized by thermal co-precipitation of ferric and ferrous chloride using two different base solutions. Glucose oxidase was bound to the particles by direct attachment via carbodiimide activation or by thiophene acetylation of magnetic nanoparticles. Transmission electron microscopy was used to characterize the size and structure of the particles whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(38 citation statements)
references
References 22 publications
2
36
0
Order By: Relevance
“…A suspension of MNPs was synthesized by co-precipitation of Fe +2 and Fe +3 ions, from appropriate mixture solution of ferrous sulfate and ferric chloride, with ammonia, as described earlier [7,19,20]. A microemulsion containing 7.2 mL of cyclohexane, 1.8 mL of n-hexanol, 1.8 mL of Triton X-100 and adequate aqueous magnetic ferrofluid (Fe 3 O 4 ) was prepared.…”
Section: Preparation Amino-modified Silica-encapsulated Mnpsmentioning
confidence: 99%
See 3 more Smart Citations
“…A suspension of MNPs was synthesized by co-precipitation of Fe +2 and Fe +3 ions, from appropriate mixture solution of ferrous sulfate and ferric chloride, with ammonia, as described earlier [7,19,20]. A microemulsion containing 7.2 mL of cyclohexane, 1.8 mL of n-hexanol, 1.8 mL of Triton X-100 and adequate aqueous magnetic ferrofluid (Fe 3 O 4 ) was prepared.…”
Section: Preparation Amino-modified Silica-encapsulated Mnpsmentioning
confidence: 99%
“…The protein concentration was determined using Bradford method. Bovine serum albumin (BSA) was used as the protein standard [7,19,28,29].…”
Section: Enzyme Immobilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…[22] The studies of different enzymes assembled onto magnetite nanoparticle surfaces have also demonstrated the potential of enhancing the enzymatic activity. [23,24] However, the investigation of the enhanced activity, stability, and active temperature range of enzymes is still limited to an initial stage.…”
Section: Introductionmentioning
confidence: 99%